(untitled) (Scientific journal of the Fergana State University, 2025)
The article studies the theoretical and methodological foundations of the formation of an enlightened society in New Uzbekistan, the socio-philosophical aspects of the formation of an enlightened society in New Uzbekistan, the future tasks of the formation of enlightenment as a high moral value in New Uzbekistan. Also, the synergistic strategy of the formation of an enlightened society in New Uzbekistan is analyzed.